Cloning and Optimized Expression of Bst DNA Polymerase from Geobacillus stearothermophillus in Escherichia coli BL21 - Taufik, Intan; Fanany, Rizal; Manjaswari, Agika; Pratama, Fenryco (HAYATI Journal of Biosciences, 2025)
Bst DNA polymerase possesses strand displacement activity, enabling isothermal DNA amplification without requiring a thermal cycler. This enzyme is utilized in the Loop-Mediated Isothermal Amplification (LAMP) method, which offers advantages in speed and simplicity over Polymerase Chain Reaction (PCR) method. The growing demand for Bst DNA polymerase highlights the need for cost-effective in-house production, as a commercial option is economically challenging. For that purpose, this study aims to construct and optimize the expression of Bst DNA polymerase from Geobacillus stearothermophilus in Escherichia coli. The expression constructs pET16b.BstHF vector was constructed using Gibson Assembly and expressed in E. coli BL21 (DE3). Optimal expression was achieved with 1 mM IPTG, induction at OD600 0.8 and 6-hour induction time. The purified enzyme was achieved with a protein yield of 2,175 mg/L culture and demonstrated effective polymerase activity for LAMP.